Disposal of Radioactive Waste Generated at the End of 18F- Fluorodeoxyglucose Production for Positron Emission Tomography - Computed Tomography (PET-CT) Scan at Armed Forces Institute of Radiology and Imaging, Rawalpindi - Bilal, Rizwan; Mehdi, Syed Ali; Slehria, Atiq ur Rehman; Ullah, Hidayat; Amin, Zafar; Jamal, Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the optimal timeline for the safe disposal of radioactive wastes generated at the end of normal and anomalous productions of 18F-Fluorodeoxyglucose for positron emission tomography-computed tomography scans.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Aug to Dec 2020.Methodology: Wastes generated at the end of 18F-Fluorodeoxyglucose production were tested for residual radioactivity at 2, 12 and 24 hours after synthesis to ascertain the optimal timeline for discarding. The radiation dose at 5 cm from the surface of the container was also assessed.Results: Fifty productions were included in the study, of which 46(92%) were normal, and 4(8%) were anomalous productions. The mean activity at 2 and 24 hours after the end of synthesis was 4.102±0.831mCi and 0.0047±0.00116mCi, respectively, in normal productions and 45.125±2.332mCi and 0.005±0.00026mCi respectively in anomalous productions. The mean radiation dose at 5cm from the surface of the container at 2 and 24 hours after the end of synthesis was 8.2107±1.665mSv/h and 0.00000966±0.00000212mSv/h in normal productions and 90.32±4.66mSv/h and 0.00975±0.0005-mSv/h respectively in anomalous productions.Conclusion: The residual radioactivity in wastes was negligible 24 hours after the end of synthesis in both normal and anomalous productions. Radioactive wastes from 18F-Fluorodeoxyglucose production should, therefore, be conserved for at least 24 hours before their disposal to the environment.